Pulse Generator Applications in Radio Over Fiber Communication Systems - Kazancili, Ugur Umur; Unverdi, N. Ozlem (IEEE, 2021)
In this study, radio over fiber (RoF) communications systems are analyzed. In system design, optical source, pulse generator, modulator, optical fiber, optical add drop multiplexer (OADM), amplifier and filter are utilized as communication system components. In this study, performances of various pulse generators are analyzed by OptiSystem 7.0 simulation software. Radio over fiber systems with various pulse generators are modeled and the effects of them on system performance are evaluated.
Keywords: Communication technologies; optical communications; radio over fiber; pulse generator; NRZ; RZ; Engineering; Telecommunications